Effectiveness of booster vaccination with inactivated COVID-19 vaccines against SARS-CoV-2 Omicron BA.2 infection in Guangdong, China: a cohort study - He, Xiaofeng; Zeng, Biao; Wang, Ye; Pang, Yulian; Zhang, Meng; Hu, Ting; Liang, Yuanhao; Kang, Min; Tang, Shixing (Frontiers in Immunology, 2023)
The effectiveness of COVID-19 vaccines is waning over time and the emergence of SARS-CoV-2 Omicron variant led to accelerated expansion of efforts for booster vaccination. However, the effect and contribution of booster vaccination of inactivated COVID-19 vaccines remain to be evaluated. We conducted a retrospective close contacts cohort study to analyze the epidemiological characteristics and Omicron infection risk, and to evaluate the effectiveness of booster vaccination of inactivated COVID-19 vaccines against SARS-CoV-2 infection, symptomatic COVID-19, and COVID-19 pneumonia during the outbreaks of Omicron BA.2 infection from February 1 to July 31, 2022 in Guangdong, China. A total of 46,547 close contacts were identified while 6.3% contracted Omicron BA.2 infection, 1.8% were asymptomatic infection, 4.1% developed mild COVID-19, and 0.3% had COVID-19 pneumonia. We found that female and individuals aged 0-17 or  60 years old were more prone to SARS-CoV-2 infection. The vaccinated individuals showed lower infection risk when compared with the unvaccinated people. The effectiveness of booster vaccination of inactivated COVID-19 vaccines against SARS-CoV-2 infection and symptomatic COVID-19 was 28.6% (95% CI: 11.6%, 35.0%) and 39.6% (95% CI: 30.0, 47.9) among adults aged ≥ 18 years old, respectively when compared with full vaccination. Booster vaccination provided moderate level of protection against SARS-CoV-2 infection (VE: 49.9%, 95% CI: 22.3%-67.7%) and symptomatic COVID-19 (VE: 62.6%, 95% CI: 36.2%-78.0%) among adults aged ≥ 60 years old. Moreover, the effectiveness of booster vaccination was 52.2% (95% CI: 21.3%, 70.9%) and 83.8% (95% CI: 28.1%, 96.3%) against COVID-19 pneumonia in adults aged ≥ 18 and ≥ 60 years old, respectively. The reduction of absolute risk rate of COVID-19 pneumonia in booster vaccination group was 0•96% (95% CI: 0.33%, 1.11%), and the number needed to vaccinate to prevent one case of COVID-19 pneumonia was 104 (95% CI: 91, 303) in adults aged ≥ 60 years old. In summary, booster vaccination of inactivated COVID-19 vaccines provides low level of protection against infection and symptomatic inadults of 18-59 years old, and moderate level of protection in older adults of more than 60 years old, but high level of protection against COVID-19 pneumonia in older adults.